Teenage Pregnancy and Its Outcome: A Scoping Review - Shalsabila, Dhea; Pamungkas, Ade Tia Bintang; Yuniasih, Dewi; Laariya, Tira Alfiani; Mawardi, Fitriana; Suprabandari, Suprabandari; Fauziyah Rahmawati, Nurul (Universitas Ahmad Dahlan, 2023)
Pregnant teenagers are deemed high risk and detrimental to motherhood and birth, as well as one of the world's major health issues, contributing to maternal and infant mortality and migration. Pregnancy Teenagers account for 11% of all births worldwide, with some large occurrences occurring in countries with intermediate income levels due to a variety of circumstances. Study The goal of this study is to learn about the effects of pregnancy on teenagers. Study This is a study scoping review that uses search tactics utilizing the keywords